Combination of Modified Clipping Technique and Selective Mapping for PAPR Reduction (International Journal of Engineering and Computer Science, 2016)
Orthogonal frequency division multiplexing (OFDM) offers high data rate and supports high data rate applications. Although OFDM has advantages over traditional communication models but it frequently suffers from PAPR. PAPR is concerned area in OFDM from two decades and vast amount of research is carried out in literature. Selective Mapping remains as effective PAPR reduction approach and in proposed method a modified clipping technique along with selective mapping is used to reduce the PAPR reduction in efficient way. Experimental shows better results over traditional state of art methods.